INCORPORATING MANAGERIAL CONTROLS INTO INTRODUCTORY COST ACCOUNTING. - Frumar, Samuel (The Accounting Review, 1962)
Abstract In recent years, there has been a desire to incorporate managerial controls into the introductory cost accounting course. Many educators have raised the objection that this cannot be done in a one semester course and if an attempt is made to introduce managerial controls, the course will be so diluted that the student will receive no benefit out of it. This article will show that managerial controls can be built into an introductory cost course. The term "managerial controls" is used in the broad sense to include more than control per se; for purposes of this discussion it is equated to "managerial accounting." The term "managerial accounting" must be defined before an attempt is made to see how it may be incorporated into a college course of introductory cost accounting. If the course is given as outlined, adequate coverage of all topics can be achieved if proper allocation is made of class time. Class time should be taken up with discussions of managerial aspects with de-emphasis on mechanics as only the major points of a problem need to be covered in class. Simple does not necessarily mean superficial and depth can be achieved by exploring the concepts under simple problem conditions.